2011
DOI: 10.3324/haematol.2011.049155
|View full text |Cite
|
Sign up to set email alerts
|

The cytotoxicity of anti-CD22 immunotoxin is enhanced by bryostatin 1 in B-cell lymphomas through CD22 upregulation and PKC- II depletion

Abstract: BackgroundIn spite of potent first-line therapies for chronic lymphocytic leukemia, treatment remains palliative and all patients frequently relapse. Treatment options for these patients are more limited. BL22 is a recombinant protein composed of the variable region of a monoclonal antibody that binds to CD22 and of PE38, a truncated Pseudomonas exotoxin. BL22 is a very potent drug already used in patients with hairy cell leukemia, whereas in chronic lymphocytic leukemia its cytotoxicity is limited by a lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 36 publications
(52 reference statements)
1
30
0
Order By: Relevance
“…Since PKCs are considered to be the putative kinases for KRAS Ser181 phosphorylation (13,20,21), we tested whether treatment with two general PKC inhibitors that are clinically relevant (Bryostatin-1 and Edelfosine; refs. [22][23][24][25][26] were able to revert tumor growth in a dephosphorylation-dependent manner.…”
Section: Pkc Inhibitors Diminish Oncogenic Kras-mediated Tumor Growthmentioning
confidence: 99%
“…Since PKCs are considered to be the putative kinases for KRAS Ser181 phosphorylation (13,20,21), we tested whether treatment with two general PKC inhibitors that are clinically relevant (Bryostatin-1 and Edelfosine; refs. [22][23][24][25][26] were able to revert tumor growth in a dephosphorylation-dependent manner.…”
Section: Pkc Inhibitors Diminish Oncogenic Kras-mediated Tumor Growthmentioning
confidence: 99%
“…No unspecific effects of the IT or the Mock-ETA′ could be demonstrated by using the control cell line U937 and a version of Pseudomonas exotoxin A known as PE38. This has been combined with the macrolide lactone bryostatin 1 for the treatment of low-grade and high-grade B cell lymphoma, with a more potent effect than each agent alone (Biberacher et al 2012). Wei et al (2000) demonstrated that pre-treatment with a radioimmunoconjugate improved the effect of an IT in vivo against human B-cell lymphoma.…”
Section: Discussionmentioning
confidence: 98%
“…Current effort is directed at better understanding the complex regulation machinery at different stages of the pathway by which immunotoxins kill cells. This knowledge may be helpful to enhance the killing effect of these immunotoxins, or even to expand them to the treatment of different malignancies [47,48].…”
Section: Brief Historical Overview Of Pe-based Itsmentioning
confidence: 99%
“…Additionally to CLL cells, the authors showed that BL22 and bryostatin 1 combined treatment exerts a strong apoptotic effect in large B-cell lymphomas and mantle cell lymphoma cells. The authors concluded that this drug synergism should be tested in vivo to evaluate if it can be a feasible therapeutic approach for CLL and B-cell malignancies [48].…”
Section: Insufficient Potency and Combining Therapies To Enhance Potencymentioning
confidence: 99%